SGP Inventory Management System - GNANA SRI ARUMUGAM; Nurul Aswa Omar (Applied Information Technology And Computer Science, 2024)
An inventory management system allows businesses to track their stocks, supplies and sales through an entire supply chain. The development of an inventory management system is necessary for SGP Store in order to resolve the inaccurate inventory tracking, stockouts and overstocking products, and to avoid the time-consuming manual processes. The objective of this project is to develop an inventory management system for SGP Store, with two targeted users, which are administrator and staff. The software development model that was used to execute this project is the famously used Waterfall model. The system will be a web-based system using HTML, CSS, and JavaScript. PHP programming language will also be used to create the system framework. Therefore, by developing this inventory management system, the SGP Store will be able to monitor their sales patterns, make well informed decisions, and react quickly to changes in the market.